Microbial Transformation of Chlordecone and Two Transformation Products Formed During in situ Chemical Reduction - Hellal, Jennifer; Saaidi, Pierre-Loïc; Bristeau, Sébastien; Crampon, Marc; Muselet, Delphine; Della-Negra, Oriane; Mauffret, Aourell; Mouvet, Christophe; Joulian, Catherine (Frontiers in Microbiology, 2021)
Chlordecone (CLD) is a very persistent synthetic organochlorine pesticide found in the French West Indies. Recently published work has demonstrated the potential of zero valent iron to dechlorinate CLD by in situ chemical reduction (ISCR) in soils under water-saturated conditions, forming mono to penta-dechlorinated CLD transformation products. These transformation products are more mobile than CLD and less toxic, however, nothing is known about their further degradation, although increasing evidence of CLD biodegradation by bacteria is being found. The present study began with the enrichment from waste-water sludge of a CLD transforming community which was then inoculated into fresh media in presence of either CLD, or two of the main ISCR transformation products, the 10-monohydroCLD (-1Cl-CLD) and a tri-hydroCLD (-3Cl-CLD). Carried out in triplicate batches, and incubated at 38°C under anoxic conditions and in the dark, the cultures were sampled regularly during three months and analyzed for CLD, -1Cl-CLD, -3Cl-CLD and possible transformation products by Gas Chromatography coupled to Mass Spectrometry. All batches showed a decrease in CLD and hydroCLD. CLD degradation occurred with concomitant formation of a 9-carbon compound (pentachloroindene) and two sulfur-containing transformation products (chlordecthiol, CLD-SH; methyl chlordecsulfide CLD-SCH3) demonstrating competing transformation pathways. In contrast, -1Cl-CLD and -3Cl-CLD underwent a sequential reductive sulfidation / S-methylation process resulting in -1Cl-CLD-SH, -1Cl-CLD-SCH3 and -1Cl-CLD-SH, -1Cl-CLD-SCH3. Some sulfur-containing transformation products have been reported previously with single bacterial strains, but never as a complex microbial community. At the end of the experiment, bacterial and archaeal populations were investigated by 16S rRNA gene amplicon sequencing. The diversity was mostly similar to the inoculum in the CLD and -1Cl-CLD conditions with a dominant archaea genus, Methanobacterium, and four OTU affiliated to bacteria, identified at the family (Spirochaetaceae) or genus level (Desulfovibrio, Aminobacterium and Soehngenia). Whereas, in the -3Cl-CLD condition, although the same OTU were found, Clostridium sensu stricto 7, Candidatus Cloacimonas and Proteiniphilum were also present at >2% sequences. Presence of methanogens and sulfate-reducing bacteria could contribute to sulfidation and S-methylation biotransformations. Overall, results contribute to increasing our knowledge on the biodegradability of CLD and its transformation products, helping to progress towards effective remediation solutions.